-(-1-5)+8=-17+2x

Simple and best practice solution for -(-1-5)+8=-17+2x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(-1-5)+8=-17+2x equation:


Simplifying
-1(-1 + -5) + 8 = -17 + 2x

Combine like terms: -1 + -5 = -6
-1(-6) + 8 = -17 + 2x

Multiply -1 * -6
6 + 8 = -17 + 2x

Combine like terms: 6 + 8 = 14
14 = -17 + 2x

Solving
14 = -17 + 2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2x' to each side of the equation.
14 + -2x = -17 + 2x + -2x

Combine like terms: 2x + -2x = 0
14 + -2x = -17 + 0
14 + -2x = -17

Add '-14' to each side of the equation.
14 + -14 + -2x = -17 + -14

Combine like terms: 14 + -14 = 0
0 + -2x = -17 + -14
-2x = -17 + -14

Combine like terms: -17 + -14 = -31
-2x = -31

Divide each side by '-2'.
x = 15.5

Simplifying
x = 15.5

See similar equations:

| 2(a+12)=4(a+6)-2a | | 6(2z-3)-4=3(5z-7) | | y+3(15-25)+25=40 | | -56x^3y^4-32x^6y^3= | | m/16=0.5 | | (4x^2-9)/(2x^2-3x) | | 3p-q=3.6 | | x+(x+12)=90 | | 4x^2-16x-y^2-2y+8z^2+8z+17=0 | | 26x^2-23xy+5y^2= | | 336-8x=13x | | 2p=-q+49 | | -1(x-6)=8x-72 | | j/12=11 | | y+2(5-25)+20=30 | | 2x^2-0=64 | | h/13=13 | | 4x^2-16x-y^2-2+8z^2+8z+17=0 | | 6x+3=2x-7-2x | | 40x^2-140=500 | | V=s^3 | | x^2+15xy+54y^2= | | 6n^2+30n-9=0 | | 2y-3-678=500 | | 6x+15x^2+6x^3=0 | | 3x+13=6y | | u^2-12u-15=0 | | 6/t^3=0 | | 6/t^3 | | 6x+-2+8=x+5 | | s^3+4*s^2+10*s+40=0 | | 4sin(3x)=2 |

Equations solver categories